Scaling of the corpus callosum in wild and domestic canids: Insights into the domesticated brain. Issue 15 (25th September 2018) - Spocter, Muhammad A.; Uddin, Ashraf; Ng, Johnny C.; Wong, Edmund; Wang, Victoria X.; Tang, Cheuk; Wicinski, Bridget; Haas, Jordan; Bitterman, Kathleen; Raghanti, Mary Ann; Dunn, Rachel; Hof, Patrick R.; et al.
Abstract: All domesticated mammals exhibit marked reductions in overall brain size, however, it is unknown whether the corpus callosum (CC), an integral white matter fiber pathway for interhemispheric cortical communication, is affected by domestication differentially or strictly in coordination with changes in brain size. To answer this question, we used quantitative magnetic resonance imaging to compare the midsagittal cross‐sectional areas of the CC in 35 carnivore species, including eight wild canids and 13 domestic dogs. We segmented rostro‐caudal regions of interest for the CC and evaluated correlations with brain mass. The results of this study indicate that under the influence of domestication in canids, the CC scales to brain size in an allometric relationship that is similar to that of wild canids and other carnivores, with relatively high correlation coefficients observed for all regions, except the rostrum. These results indicate that architectural and energetic considerations are likely to tightly constrain variation in caudal components of the CC relative to overall brain size, however fibers passing through the rostrum, putatively connecting prefrontal cortex, are less constrained and therefore may contribute more toward species‐specific differences in connectivity. Given the species diversity of the Canidae and the resurgence of interest in the brain of the domestic dog, further studies aimed at characterizing the neural architecture in domesticated species is likely to provide new insights into the effects of domestication, or artificial selection, on the brain. Abstract : The study of domestic animals provides an opportunity to evaluate the effect of artificial selection on the brain. Using image analysis techniques, we compared scaling of the CC in wild and domestic canids and show that the rostrum, putatively connecting the prefrontal cortex, is less constrained by brain size.